TRYPANOCIDAL, ANTI-LEISHMANIAL, AND CYTOTOXIC ACTIVITY OF MUEHLENBECKIA TAMNIFOLIA (KUNTH) MEINS (POLYGONACEAE) - E. RODRÍGUEZ, OSCAR; D. TORRENEGRA, RUBÉN; M. POMBO, LUIS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the activity against amastigotes of Leishmania panamensis and epimastigotes of Trypanosoma cruzi (Chagas), extracts and fractions obtained from leaves and stems of Muehlenbeckia tamnifolia. Methods: Plant material was collected during the flowering, in the town of La Calera (Cundinamarca), at a height of 2746 m above sea level, 4°43’11”N, 3°58’12”W. Leaves and stems were extracted with light petroleum and then with ethanol. The extracts were fractionated by column chromatography on silica gel with petrol; CH2Cl2, AcOEt, and MeOH. The activity against epimastigotes and cytotoxicity was evaluated by the enzymatic micromethod with MTT. The active extracts against epimastigotes and with low cytotoxicity were also evaluated in trypomastigotes and intracellular amastigotes. Results: The dichloromethane fraction from leaves and stems of M. tamnifolia showed the highest activity against Leishmania panamensis with an 50% of the effective concentration of 0.006 (μg/ml) and a selectivity index of 4.16. In U937 cells, six of the extracts and fractions tested showed high cytotoxicity, 50 inhibitory concentration <50 μg/ml. Conclusions: The extracts obtained from leaves and stems of different polarities of M. tamnifolia (Kunth) Meins, revealed a moderate effect against amastigotes of L. panamensis (Leishmaniosis) (low polarity fractions) and a low effect against epimastigotes of T. cruzi (Chagas).